Peran Suasana Klinik, Persepsi Harga, dan Kualitas Layanan dalam Meningkatkan Loyalitas Pelanggan Meutia Beauty Centre - Wirda Tul Jannah; Tengku Putri Lindung Bulan; Rahmi Meutia (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2025)
This research aims to determine the role of clinic atmosphere, price perceptions and service quality in increasing Meutia Beauty Center customer loyalty. In this study, 100 respondents were used as samples. The data analysis methods used include multiple linear regression, t test, F test and coefficient of determination test (Adjusted R2). The research results show that the clinic atmosphere variable has a significant effect in increasing Meutia Beauty Center customer loyalty, the price perception variable has a significant effect in increasing Meutia Beauty Center customer loyalty, and the service quality variable has a significant effect in increasing Meutia Beauty Center customer loyalty. The F test revealed that simultaneously the clinic atmosphere, price perception and service quality had a significant effect in increasing Meutia Beauty Center customer loyalty, apart from that the coefficient of determination (Adjusted R2) obtained was 0.591 or 59.1% of customer loyalty could be explained by these factors, while the remaining 40.9% was influenced by other variables not examined in this research.